Electrochemical capacitance of nanocomposite films formed by loading carbon nanotubes with ruthenium oxide - Lee, Jae-Kyung; Pathan, Habib M.; Jung, Kwang-Deog; Joo, Oh-Shim (ELSEVIER, 2006)
This work reports the supercapacitive properties of composite films of multiwalled carbon nanotubes (MWNT) and ruthenium oxide (RuO2). Transmission and scanning electron microscopy, cyclic voltammetry, and electrochemical studies revealed that the nanoporous three-dimensional arrangement of RuO2-coated MWNT in these films facilitated the improvement of electron and ion transfer relative to MWNT films. The capacitance was measured for films of different RuO2 loading, revealing specific capacitances per mass as high as 628 F g(-1). The energy storage density of the electrode has increased about three times as compared to MWNT treated with piranha solution. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: COMPOSITE ELECTRODES; SUPERCAPACITORS; PERFORMANCE; AEROGELS